The characteristics of androgen receptor splice variant 7 in the treatment of hormonal sensitive prostate cancer: a systematic review and meta-analysis - Zhize Wang; Haixiang Shen; Zhen Liang; Yeqing Mao; Chaojun Wang; Liping Xie (Cancer Cell International, 2020)
Abstract Background Accumulating evidence suggests androgen receptor splice variant 7 (AR-V7) may be associated with the prognosis of castration-resistant prostate cancer (CRPC) received novel hormonal therapy while its characteristic and prognosis value in hormonal sensitive prostate cancer is unclear. Methods We aimed to evaluate the prognostic role of AR-V7 by progression free survival (PFS) and overall survival (OS) in hormonal sensitive prostate cancer (HSPC), and the AR-V7-positive-proportion difference in HSPC and CRPC. A search of PubMed, Embase, and the Web of Science was performed using the keywords prostate cancer, prostate tumor, prostate neoplasm, prostate carcinoma; AR-V7, AR3, androgen receptor splicing variant-7, or androgen receptor-3. Seventeen trials published due December 2019 were enrolled. Results AR-V7-positive proportion in CRPC was significantly larger than newly diagnosed prostate cancer (PCa) (odds ratio [OR] 7.06, 95% confidence interval [CI] 2.52–19.83, P < 0.001). Subgroup analyses indicated significantly higher AR-V7-positive proportion in CRPC derived from RNA in situ hybridization (OR 65.23, 95% CI 1.34–3171.43, P = 0.04), exosome RNA (OR 3.88, 95% CI 0.98–15.39, P = 0.05) and tissue RNA (OR 10.89, 95% CI 4.13–28.73, P < 0.001). AR-V7-positive patients had a significantly shorter PFS than those who were AR-V7-negative treated with first-line hormonal therapy (hazard ratio [HR] 3.63, 95% CI 1.85–7.10, P < 0.001) and prostatectomy (HR 2.49, 95% CI 1.33–4.64, P = 0.004). OS (HR 5.59, 95% CI 2.89–10.80, P < 0.001) were better in AR-V7-negative than AR-V7-positive HSPC patients treated with first-line hormonal therapy. The limitations of our meta-analysis were differences in study sample size and design, AR-V7 detection assay, and disease characteristics. Conclusion AR-V7-positive proportion was significantly higher in CRPC than that in newly diagnosed PCa. AR-V7 positive HSPC patients portend worse prognosis of first-line hormonal therapy and prostatectomy. Additional studies are warranted to confirm these findings.